STRATEGI HUMAS DALAM MEMPERTAHANKAN KEPERCAYAAN MASYARAKAT DI ERA SOCIETY 5.0 - Riki Habibi; Moh. Rifa’i (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to analyze public relations strategies in maintaining public trust in the Society 5.0 era at SMA Nurul Jadid Pragaan Sumenep. A qualitative descriptive approach was employed. Data were collected through in-depth interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings reveal three main strategies implemented by the school: (1) transparent and responsive digital communication through social media platforms to facilitate information access and public interaction; (2) dissemination of credible digital content that strengthens the institution’s image and credibility; and (3) collaborative engagement involving parents, alumni, and community leaders in school activities. These strategies contribute to strengthening public trust, increasing stakeholder participation, and fostering sustainable relationships between the school and the community. This study contributes to the development of integrated public relations practices in educational institutions by emphasizing the synergy between digital communication, content credibility, and public participation in the Society 5.0 era.